A higher education student-choice analysis: the case of Lebanon. (2016) - Nemar, Sam El; Vrontis, Demetris
The purpose of this study was to develop a conceptual framework for student choices for Lebanon. From the existing identified student choice frameworks none directly combine factors of influence, decision making process and information gathering as a total model. This enhanced framework will provide direction for Lebanese universities to recruit new students through institutional marketing. The objectives of this article are: to examine the factors identified in the literature that would influence/affect student choices in selecting higher education, and secondly to identify existing student choice models (SCM) and then develop a conceptual framework to help assist Lebanese universities in marketing their institutions. This article employed a deductive approach, focusing on secondary data. The parent literature revealed the combination model which magnifies the dimensions of student university influence, Hossler et al. (1999). The limitation of this study is the testing and validation of the conceptual model, further research should focus on testing and validating the proposed conceptual model on Lebanese students.